PERENDAMAN IKAN LELE SANGKURIANG (Clarias sp.) DALAM SARI BUAH BELIMBING WULUH UNTUK MENGOBATI INFEKSI Aeromonashydrophila - Linda Purnamasari; ade dwi sasanti; yulisman . (Universitas Sriwijaya, 2015)
ABSTRACT Aeromonashydrophila is a bacteria that causes Motile Aeromonas Septicaemia (MAS)and infecting freshwater fish, especially catfish. The aims of this research were totest efectivness of Avverhoa bilimbijuice for bacterial infections Aeromonas hydrophila treatmentin Catfish (Clarias sp.). The implementation of this research wasfrom September until November 2014 in Budidaya Perairan Laboratory,Aquaculture Study Program, Agriculture Faculty, Sriwijaya University and blood testinUPTKlinik Kesehatanof Sriwijaya University.The research usedCompletelyRandomized Design with six treatments and three replications. The research usedÂ immersion treatments with 0.05%, 0.1%, 0.15%, 0.2%, 0.25% and 0.3% during 24 hours. Parameters observed were percentage of healed fish andsurvival rate. The results showed that treatment throughimmersionmethodcatfishinAvverhoa bilimbijuice caused bacterial A.hydrophilainfection as much 0,2% fasterheal the woundscaused bacterialof A.hydrophilainfection withthe highestpercentage ofhealedfish91,11% andthe percentage ofthe best survivalrate at 93,33%. Â Keywords :Catfish,Avverhoa bilimbi juice,A.hydrophila,Treatments.